ECONOMIC INDICATORS OF SEMI-HARD AND HARD CHEESE PRODUCTION IN SMALL-SCALE DAIRY PROCESSORS IN SERBIA - Milić, Dragan; Glavaš - Trbić, Danica; Tomaš Simin, Mirela; Zekić, Vladislav; Novaković, Tihomir; Vukelić, Nataša (Journal of Agricultural Sciences (Belgrade), 2020)
Animal husbandry has a longstanding tradition in Serbia, and the production of milk and dairy products has a rich legacy. In terms of quantity, cattle consumer milk is prevalent at the market and it is used in the manufacture of all kinds of dairy products. Annual global cheese production is about 20 million tons, with cattle milk cheeses produced in large-scale processing plants constituting about 80% of that production. In Serbia, leaders of milk production are small family dairy farms, which contribute 92% of total production, while dairies with large capacity dominate in milk processing. There are 211 milk processing plants of varying capacity in Serbia. The largest amounts of milk are processed by dairy plants “Imlek” and “Subotica”, while 188 small-scale dairies process 20% of total milk. This paper aims to investigate economic indicators of processing milk into semi-hard and hard cheese in small-scale processors in Serbia. The study has revealed that cost price of semi-hard and hard cheese in a small-scale dairy processor amounts to 3.33 €/kg. With 90.83% in the structure of total costs of processing milk into cheese, the cost of raw materials has the largest share, followed by labor costs with 6.54%. In order for small-scale dairy processors to become as competitive as large-scale ones in contemporary market conditions, they should pay utmost attention to direct material costs and purchase raw materials at lower prices without sacrificing their quality and ultimately the quality of dairy products. Key words: hard cheese, semi-hard cheese, economic indicators of production, small-scale dairy, competitiveness.